Von Hippel‐Lindau development in children and adolescents. Issue 9 (26th June 2017) - Launbjerg, Karoline; Bache, Iben; Galanakis, Michael; Bisgaard, Marie Luise; Binderup, Marie Louise M.
Abstract : The autosomal dominant von Hippel‐Lindau disease (vHL) is associated with a lifelong risk of tumor development, especially retinal and CNS hemangioblastomas, pheochromocytoma, and renal cell carcinoma. Knowledge of paediatric vHL development is limited, and current surveillance guidelines are based on expert opinions. We aimed to describe the course of vHL development in children and adolescents, focusing on age at first manifestation, manifestation frequencies, and types. The prevalence of vHL diagnosis as well as manifestations in childhood were evaluated based on 99 patients, who had started surveillance before 18 years: 37 Danish patients from the national vHL research database and 62 international patients reported in 15 articles. Overall, 70% (69 of 99) developed manifestations before 18 years (median age at first manifestation: 12 years (range: 6–17 years)). Thirty per cent (30 of 99) had developed more than one manifestation type; the most frequent were retinal (34%) and CNS (30%) hemangioblastomas. Among the 37 Danish patients, 85% (97 of 116) of their tumors were asymptomatic. Vision outcome is significantly improved in hemangioblastomas that are treated while still asymptomatic. We agree with current guidelines that retinal surveillance be performed from birth. The patients had their first CNS hemangioblastomas at the median ages of 13–14 years (range: 6–17 years). Further, 11% (4 of 37) of the Danish patients had CNS surgery in their teenage years. Although the cohort is too small to make definite conclusions about specific initiation ages, regular CNS surveillance from vHL patients' teenage years seems clinically relevant.